The Impact of Active Bystander Training on Officer Confidence and Ability to Address Ethical Challenges. (11th April 2022) - Taniguchi, Travis; Vovak, Heather; Cordner, Gary; Amendola, Karen; Yang, Yukun; Hoogesteyn, Katherine; Bartness, Martin
Abstract: Active bystandership (AB) training in the Baltimore Police Department (titled Ethical Policing is Courageous, (EPIC)) was designed to (1) prevent misconduct, (2) avoid mistakes, and (3) promote healthy officers. AB training promotes an organizational culture where officers feel empowered to intervene when noticing their colleagues are or are about to, engage in dangerous, unwanted, or inappropriate behaviour. It focuses on direct intervention in an informal capacity rather than formalized reporting. Self-report surveys ( n = 1, 753) were collected immediately post-completion of EPIC training. Survey domains included perceived impact of the training on behaviour, application to the job, confidence in ability to intervene, and ability to address ethical challenges. A large majority of respondents indicated greater likelihood of intervening after the training and having confidence in their ability to intervene with peers and supervisors; write-in responses suggested that the biggest perceived challenge was in intervening with supervisors.